Integrating STPA with Safety Requirements Modeling - Ribeiro, Moniky; Castro, Jaelson; Argenton, Ricardo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2024)
Context: Requirements modeling is essential for Safety-Critical Systems because accidents are often due to inaccurate, incomplete or inconsistent requirements. The main reason of bad requirements is poor communication between safety engineers and requirements engineers. Objective: Our goal is to propose an approach that enable safety requirements to reflect the findings of the initial safety analysis phase. Method: We integrate two techniques 1) iStar4Safety, a goal-oriented requirements modeling language tailored for safety requirements and 2) STPA (System Theoretic Process Analysis), a well-recognized and accepted safety analysis technique. Results: Through this integration, our framework promises a more systematic and comprehensive approach to modeling early safety requirements. It supports the elicitation and analysis of safety concerns, fosters stakeholder communication, and underpins the development of inherently safer and more reliable critical systems. Conclusions: A real project, related to development of a low-cost Insulin Infusion Pump System - IIP, serves as example to illustrate the effectiveness of the proposed approach. Preliminary results indicates that the approach contributes to improving the visualization of the safety related information generated in the safety analysis such as the accidents, system level hazards, hazard causes, hazard mitigations, and safety requirements.